Effects of oxygen vacancies on polarization stability of barium titanate - Wang, J.; Shen, Y.; Song, F.; Ke, F.; Bai, Y.; Lu, Chunsheng (2016)
© 2016, Science China Press and Springer-Verlag Berlin Heidelberg. Oxygen vacancy, a kind of native point defects in ferroelectric ceramics, usually causes an increase of the dielectric loss. Based on experimental observations, it is believed that all of the oxygen vacancies are an unfavorable factor for energy saving. By using molecular dynamics simulations, we show that the increase of coercive and saturated electric fields is due to the difficulty to switch local polarization near an oxygen vacancy, and so that a ferroelectric device has to sustain the rising consumption of energy. The simulation results also uncover how oxygen vacancies influence ferroelectric properties.